Composition

By developing a composition containing solvents and carbonizable organic materials, the thermal control problem in multi-heating element products is solved, effective response and propagation prevention to abnormal thermal events is achieved, and the operability and stability of the product are ensured.

CN119654183APending Publication Date: 2025-03-18LG CHEM LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380058107.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-29
Filing Date
2023-09-27
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively handle heat treatment, maintenance and control in products composed of multiple heating elements, especially in preventing the impact of abnormal heating, ignition and explosion on adjacent components.

Method used

A composition is developed that comprises a solvent and a carbonizable organic material for blocking heat propagation through heat exchange and formation of carbides in response to abnormal heat generation, ignition and explosion.

Benefits of technology

The composition is capable of responding to abnormal thermal events effectively, preventing its propagation to other adjacent elements, and ensuring excellent operability and storage stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005262853700000211
    Figure BDA0005262853700000211
  • Figure BDA0005262853700000281
    Figure BDA0005262853700000281
  • Figure BDA0005262853700000282
    Figure BDA0005262853700000282
Patent Text Reader

Abstract

The present specification discloses a composition for use in a product or element that generates heat or has a potential for ignition or explosion during the driving, storage and / or maintenance process, thereby being able to effectively respond to heat, ignition and explosion. For example, the composition is applied to an article comprising a plurality of products or elements so as to be able to respond to abnormal heat, explosion and fire occurring in any one of the elements or products and prevent or minimize the propagation of such heat, explosion and fire to other adjacent elements or products. The composition also exhibits excellent operability and storage stability. The present specification may also provide uses of the composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application has the benefit of priority based on Korean Patent Application Nos. 10-2022-0125266 and 10-2022-0125271, filed on September 30, 2022, and Korean Patent Application No. 10-2023-0041417, filed on March 29, 2023, the disclosures of which are incorporated herein by reference in their entirety.

[0002] This specification discloses compositions and uses thereof. Background Art

[0003] Technologies for handling heat generated by products are becoming increasingly important, but handling, maintaining and controlling heat in products composed of multiple heat generating elements (heating elements) is a difficult problem.

[0004] For example, a battery module or battery pack includes a plurality of battery cells or a plurality of battery modules positioned adjacent to each other. Therefore, heat, fire and / or explosion generated by one battery cell or battery module may affect other adjacent components and, in some cases, may cause problems such as chain fire or chain explosion. In such products, it is necessary to prevent heat, explosion or fire generated by one component from affecting other adjacent components. Summary of the invention

[0005] Technical issues

[0006] The present specification discloses a composition and its use. The present specification is intended to disclose such a composition: the composition is applied to a product or component with the possibility of abnormal heating, fire and / or explosion during driving, storage and / or maintenance process, so as to effectively respond to heating, fire and explosion.

[0007] For example, the composition disclosed in this specification is applied to an article including a plurality of products or components, so as to be able to respond to abnormal heating, explosion and / or fire occurring in any one component or product, and prevent or minimize the spread of such heating, explosion and / or fire to other adjacent components or products.

[0008] Furthermore, an object of the present application is to provide such a composition so as to ensure excellent handleability and storage stability. Furthermore, an object of the present application is to provide a use of such a composition.

[0009] Technical Solution

[0010] Among the physical properties mentioned in this specification, unless otherwise specified, the physical properties in which temperature affects the physical properties are physical properties measured at room temperature.

[0011] In this specification, the term room temperature is a natural temperature without heating or cooling, which means, for example, any temperature in the range of about 10°C to 30°C, for example, a temperature around about 23°C or about 25°C.

[0012] Unless otherwise specified herein, the temperature unit mentioned herein is °C.

[0013] Among the physical properties mentioned in this specification, unless otherwise specified, when pressure affects the results, the relevant physical properties are physical properties measured under normal pressure.

[0014] In this specification, the term normal pressure is a natural pressure without pressurization or depressurization, wherein a degree generally within a range of about 700 mmHg to 800 mmHg is referred to as normal pressure.

[0015] In the physical properties mentioned in this specification, unless otherwise specified, when humidity affects the result, the relevant physical properties are physical properties measured at humidity under standard conditions. Humidity under standard conditions means a relative humidity of about 40%, 50%, 60% or 65%.

[0016] This specification discloses compositions. Fire extinguishing compositions are compositions that are capable of responding to abnormal heating, fire and / or explosion occurring in any target.

[0017] The composition may include a solvent. When a target adjacent to the composition generates heat, catches fire, and / or explodes, the solvent may be used to reduce heat by heat exchange, etc., or to remove flames generated by the fire and / or explosion. Such a solvent may enable the composition to exhibit latent heat as described below, and when a carbonizable organic material as described below is included, it may also ensure that the organic material can effectively form carbides at the necessary time point.

[0018] For example, the solvent may be an evaporable solvent. When heat is applied to the solvent due to abnormal heating, fire and / or explosion, the solvent evaporates by the heat, and the gas generated thereby may reduce heat or be applied to remove the flame. In addition, desired latent heat may occur during the evaporation process.

[0019] As the solvent, any non-flammable solvent can be used without particular limitation. For example, a solvent having a freezing point and / or boiling point within a predetermined range can be used as the solvent.

[0020] For example, in order for the solvent to effectively respond to heat generation, fire and / or explosion, it needs to exist in a liquid phase at least at the point in time when heat generation, fire and explosion occur, and for this purpose, the freezing point of the solvent can be controlled.

[0021] For example, the lower limit of the freezing point of the solvent may be -5°C, -4°C, -3°C, -2°C, -1°C, or about 0°C, and the upper limit thereof may be about 10°C, 9°C, 8°C, 7°C, 6°C, 5°C, 4°C, 3°C, or 2°C. The freezing point may be in a range less than or equal to, or less than any of the above upper limits; in a range greater than or equal to, or greater than any of the above lower limits; or in a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. The freezing point may be evaluated according to the contents described in "2. Freezing Temperature Measurement" of the Examples section of this specification.

[0022] In order for the solvent to effectively respond to exotherm, fire and / or explosion, it may be advantageous for it to be a solvent that can be evaporated by heat generated by at least exotherm, fire and explosion, for which purpose the boiling point of the solvent may be controlled.

[0023] The lower limit of the boiling point of the solvent may be about 80° C., 85° C., 90° C., or 95° C., and the upper limit thereof may be about 120° C., 115° C., 110° C., or 105° C. The boiling point may be in the range of less than or equal to, or less than any of the above upper limits; in the range of greater than or equal to, or greater than any of the above lower limits; or in the range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.

[0024] As the solvent, an appropriate type may be selected and used without particular limitation as long as it has a freezing point and / or boiling point within the above range and is non-flammable.

[0025] Representative examples of the non-flammable solvent having a freezing point and / or boiling point within the above range include water, and thus, water may be used as the solvent, but the type of applicable solvent is not limited thereto.

[0026] The lower limit of the ratio of the solvent in the composition can be, for example, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt%, 75 wt%, or about 80 wt%, and the upper limit can be about 95 wt%, 90 wt%, 85 wt%, 80 wt%, 75 wt%, 70 wt%, 65 wt%, 60 wt%, 55 wt%, 50 wt%, 45 wt%, or about 40 wt%. The ratio can be in the range of less than or equal to, or less than any one of the above upper limits; in the range of greater than or equal to, or greater than any one of the above lower limits; or in the range of less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits.

[0027] The composition may contain additional ingredients for ensuring a proper fire extinguishing function and / or for viscosity properties (thixotropic index properties, etc.).

[0028] For example, the composition may comprise a water-absorbing polymer as a further ingredient.

[0029] The water-absorbing polymer is a polymer having the property of being able to absorb water.

[0030] In one example, the water-absorbing polymer may be a so-called hydrogel polymer or hydrogel, which is generally defined as a cross-linked hydrophilic polymer. Such polymers are also referred to as SAP (Super Adsorbent Polymer).

[0031] The water-absorbent polymer is a material that can absorb water several tens to several thousand times its own weight. Such a material allows the composition of the present application to exist as a gel as a whole, thereby exhibiting desired viscosity characteristics, and thus fulfilling the function of ensuring handleability and storage stability.

[0032] In the present application, the type of applicable water-absorbing polymer is not particularly limited, and any polymer generally usable as SAP may be used without limitation.

[0033] Generally, a polyacrylate-based vinyl polymer is used as the material. Here, the polyacrylate-based polymer is a polymer made from an acrylate-based monomer, and if necessary, other comonomers may also be used to form the polymer.

[0034] The water absorption characteristics can be adjusted so that the water-absorbing polymer exhibits properties suitable for the present application.

[0035] For example, the lower limit of the Centrifuge Retention Capacity (CRC) of the water-absorbent polymer according to EDANA (European Disposables and Nonwovens Association) method WSP 241.3 can be about 12 g / g, 13 g / g, 14 g / g, 15 g / g, 16 g / g, 17 g / g, 18 g / g, 19 g / g, 20 g / g, 21 g / g, 22 g / g, 23 g / g, 24 g / g, 25 g / g, 26 g / g, 27 g / g, 28 g / g, 29 g / g, 30 g / g, 31 g / g, 32 g / g, or 33 g / g, and the upper limit thereof can be about 60 g / g, 55 g / g, 50 g / g, 45 g / g, 40 g / g, or 35 g / g. The centrifuge retention capacity (CRC) may be in the range of less than or equal to, or less than any of the above upper limits; in the range of greater than or equal to, or greater than any of the above lower limits; or in the range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. The centrifuge retention capacity (CRC) of the water-absorbent polymer can be measured according to the method described in "8. CRC (Centrifuge Retention Capacity)" of the Examples section in this specification.

[0036] For example, the lower limit of the absorbency under pressure (AUP) of the water-absorbent polymer according to EDANA (European Disposables and Nonwovens Association) method WSP242.3 at 0.3 psi can be 4 g / g, 6 g / g, 8 g / g, 10 g / g, 12 g / g, 14 g / g, 16 g / g, 18 g / g, 20 g / g, 22 g / g, 24 g / g, 26 g / g, 27 g / g, or 28 g / g, and the upper limit thereof can also be 40 g / g, 38 g / g, 36 g / g, 34 g / g, 32 g / g, or 30 g / g. The absorbency under pressure (AUP) can be in the range of less than or equal to, or less than any of the above upper limits; in the range of greater than or equal to, or greater than any of the above lower limits; or in the range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. The absorbency under pressure (AUP) of the water-absorbent polymer can be measured according to the method described in "9. AUP (Absorption Under Pressure)" of the Example section in the present specification.

[0037] The water-absorbent polymer having the above absorbency may be combined with other components of the composition of the present application to exhibit desired characteristics.

[0038] In one example, the water-absorbing polymer may be a particulate polymer. By applying the water-absorbing polymer, the weight-based size distribution of the particulate water-absorbing polymer may be controlled to ensure desired viscosity characteristics and fire extinguishing function. In the present specification, the term weight-based size distribution of water-absorbent polymer is a size distribution measured according to the description of "17. Weight-based size distribution of water-absorbent polymer" in the Example section of the present specification, which means a size distribution in which a granular water-absorbent polymer sample is divided into a particle fraction having a size of less than 150 μm (hereinafter may be referred to as "A particle fraction"), a particle fraction in the range of 150 μm to 300 μm (hereinafter may be referred to as "B particle fraction"), a particle fraction in the range of 300 μm to 600 μm (hereinafter may be referred to as "C particle fraction"), a particle fraction in the range of 600 μm to 850 μm (hereinafter may be referred to as "D particle fraction"), and a particle fraction exceeding 850 μm (hereinafter may be referred to as "E particle fraction"), and the weight of each particle fraction is expressed as a percentage relative to the weight of the entire granular water-absorbent polymer sample (the weight ratio of each particle fraction). The weight-based size distribution can be obtained according to the EDANA method WSP 220.3 standard as described in "17. Weight-based size distribution of water-absorbing polymers" in the Examples section above.

[0039] In the weight-based size distribution, the maximum weight size of the particulate water-absorbent polymer may be in the range of 150 μm to 850 μm. Here, the maximum weight size is the size of the particle size showing the highest weight ratio among the weight ratio of the A particle size, the weight ratio of the B particle size, the weight ratio of the C particle size, the weight ratio of the D particle size, and the weight ratio of the E particle size. That is, the case where the maximum weight size is in the range of 150 μm to 850 μm means that the weight ratio of the particulate water-absorbent polymer belonging to any one of the B particle size, the C particle size, and the D particle size, or two or more, shows the maximum value. Since the weight ratios of the two particle sizes are the same, and their weight ratios may also represent the highest value among the weight ratios of all the particle sizes, the particle size having the maximum weight size may also be one, two, or more. In one example, the particle size having the maximum weight size may be the C particle size among the B particle size, the C particle size, and the D particle size. Therefore, the maximum weight size in the weight-based size distribution may also be in the range of 300 μm to 600 μm.

[0040] The weight ratio of the particle fraction representing the largest weight size in the weight-based size distribution of the particulate water-absorbent polymer (i.e., the weight ratio of the water-absorbent polymer belonging to the largest weight size in the weight-based size distribution) may have a lower limit of about 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt%, 71 wt%, 72 wt%, 73 wt%, or 74 wt%, and an upper limit thereof may be about 95 wt%, 90 wt%, 85 wt%, 80 wt%, 79 wt%, 78 wt%, 77 wt%, 76 wt%, or 75 wt%. The weight ratio may be in the range of greater than or equal to, or greater than any of the above lower limits; or in the range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.

[0041] If the maximum weight size is too small and / or the weight ratio of the particle size representing the maximum weight size is too small, the composition may not properly form a desired gel, thereby possibly reducing handling and storage characteristics, or it may not be able to exert a fire extinguishing function, so that an appropriate particulate water-absorbent polymer may be selected in consideration of this problem.

[0042] The lower limit of the weight ratio of the water-absorbent polymer to 100 parts by weight of the solvent may be about 0.5 parts by weight, 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, or 9 parts by weight, and the upper limit thereof may be about 30 parts by weight, 29 parts by weight, 28 parts by weight, 27 parts by weight, 26 parts by weight, 25 parts by weight, 24 parts by weight, 23 parts by weight, 22 parts by weight, 21 parts by weight, 20 parts by weight, 19 parts by weight, 18 parts by weight, 17 parts by weight, 16 parts by weight, 15 parts by weight, 14 parts by weight, 13 parts by weight, 12 parts by weight, 11 parts by weight, 10 parts by weight, 9 parts by weight, 8 parts by weight, or 7 parts by weight. The ratio may be within a range of less than or equal to, or less than any of the above upper limits; within a range of greater than or equal to, or greater than any of the above lower limits; or within a range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.

[0043] The composition may include additional ingredients to ensure proper fire extinguishing function. For example, the composition may include a carbonizable organic material. The carbonizable organic material forms a carbide at a necessary time point (i.e., a time point when it is necessary to respond to abnormal heating, ignition and / or explosion). The carbide thus formed can hinder heat transfer. In one example, by applying the carbonizable organic material in a solvent together with the carbonization catalyst generator described below, it is also possible to obtain an effect of allowing the formation of carbides that can effectively respond to abnormal heating, ignition and / or explosion even when a small amount of carbonizable organic material is applied.

[0044] As the carbonizable organic material, any appropriate type may be applied without particular limitation as long as it is a material that forms carbide when exposed to heat or flame.

[0045] In one example, as a carbonizable organic material (e.g., starch to be described below), a carbonizable organic material having a gelatinization viscosity within a certain range can be used. Such a gelatinization viscosity is related to the characteristics of the carbonizable organic material when present in a solvent, wherein carbides can be formed more efficiently by controlling the gelatinization viscosity. In addition, the viscosity and thixotropic index of the composition can also be adjusted to an appropriate level by controlling the gelatinization viscosity. The lower limit of the gelatinization viscosity of the carbonizable organic material (e.g., starch) may be about 150, 200, 250, 300, 350, 400, 450, 500, 550, 650, 700, 750, 800, 850, 900, 950, or 1,000, and the upper limit thereof may be about 5,000, 4,500, 4,000, 3,500, 3,000, 2,500, 2,000, 1,500, 1,000, 950, 900, 850, 800, 750, 700, 650, 600, 550, 500, 450, 400, 350, or 300. The gelatinization viscosity may be in a range of less than or equal to, or less than any of the above upper limits; in a range of greater than or equal to, or greater than any of the above lower limits; or in a range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. The gelatinization viscosity can be measured by the method described in "16. Evaluation of gelatinization viscosity" in the Examples section of this specification, wherein the unit is BU (Brabender unit).

[0046] Examples of such organic materials may be exemplified by sugars such as sorbitol or mannitol, polysaccharides such as starch or dextrin (e.g., MC (maleated cyclodextrin) or metal salts of MC, etc.), polyols such as pentaerythritol, dipentaerythritol, tripentaerythritol, or THEIC (tris(hydroxyethyl)isocyanurate), cellulose, BSPPO (bis(4-methoxy-1-phospha-2,6,7-trioxabicyclo[2.2.2]-octane-1-sulfide)phenyl phosphate), lignin (alkali lignin or urea-modified lignin, etc.), melamine compounds such as hydroxymethyl melamine, phenolic resins and / or carbonizable polymers (char-forming polymers) such as PA6T (poly-hexa methylene terephthalamide), but are not limited thereto.

[0047] A material that can be generally applied as the carbonizable organic material is starch. Starch is relatively easy to obtain and can form a suitable carbide when exposed to heat or flame.

[0048] The type of starch can be adjusted so that carbide is effectively formed and the formed carbide effectively exerts the desired fire extinguishing or insulating effect.

[0049] For example, as starch, starch containing straight-chain starch and amylopectin can be used, and its ratio is adjusted to an appropriate level. As known, amylopectin and straight-chain starch are polysaccharide types mainly present in plants, and the starch of polysaccharide is composed of straight-chain starch and amylopectin. Stranded-chain starch is composed of glucose molecules connected by α (1→4) glycosidic bonds and has a linear chain structure, while amylopectin has a relatively short and highly branched chain. Compared with amylopectin, straight-chain starch is relatively easy to crystallize, and the solubility of amylopectin in water is relatively higher than that of straight-chain starch.

[0050] By using the starch that the straight-chain starch and amylopectin with the above characteristics exist in an appropriate ratio, the desired composition can be provided more effectively. For example, in the starch comprising straight-chain starch and amylopectin, the lower limit of the weight ratio of amylopectin relative to 100 weight portions of straight-chain starch can be 150 weight portions, 200 weight portions, 250 weight portions, or about 300 weight portions, and its upper limit can be 900 weight portions, 850 weight portions, 800 weight portions, 750 weight portions, 700 weight portions, 650 weight portions, 600 weight portions, 550 weight portions, 500 weight portions, 450 weight portions, 400 weight portions, 350 weight portions, or about 300 weight portions. The ratio can be in the range of less than or equal to or less than any one of the above-mentioned upper limits; in the range of greater than or equal to or greater than any one of the above-mentioned lower limits; or in the range of less than or equal to or less than any one of the above-mentioned upper limits, and greater than or equal to or greater than any one of the above-mentioned lower limits at the same time. The ratio of amylose to amylopectin can be measured by the method described in "11. Measurement of amylopectin and amylose contents" in the Example section of the present specification.

[0051] As starch, starch with a molecular weight within a predetermined range, such as a weight average molecular weight (Mw), can be used. For example, the lower limit of the weight average molecular weight of starch can be 200,000 g / mol, 250,000 g / mol, 300,000 g / mol, 350,000 g / mol, 400,000 g / mol, 450,000 g / mol, 500,000 g / mol, 550,000 g / mol, 600,000 g / mol, 650,000 g / mol, 700,000 g / mol, 750,000 g / mol, 800,000 g / mol, 850,000 g / mol, 900,000 g / mol, 1000,000 g / mol, 1100,000 g / mol, 1110,000 g / mol, 1120,000 g / mol, 1130,000 g / mol, 1140,000 g / mol, 1150,000 g / mol, 1160,000 g / mol, 1170,000 g / mol, 1180,000 g / mol, 1190,000 g / mol, 1210,000 g / mol, 1220,000 g / mol, 1230,000 g / mol, 1240,000 g / mol, 1250,000 g / mol g / mol, 950,000g / mol, 1,000,000g / mol, 1,500,000g / mol, 2,000,000g / mol, 2,500,000g / mol, 3,000,000g / mol, 3,500,000 g / mol, 4,000,000g / mol, 4,500,000g / mol, 5,000,000g / mol, 5,500,000g / mol, 6,000,000g / mol, 6,500,000g / mol, 7,000,00 The molecular weight of the present invention may be about 10 g / mol, 20 g / mol, 30 g / mol, 40 g / mol, 50 g / mol, or 60 g / mol, and the upper limit thereof may be about 1,000,000,000 g / mol, 900,000,000 g / mol, 10,000,000 g / mol, 20,000,000 g / mol, 30,000,000 g / mol, 40,000,000 g / mol, or 50,000,000 g / mol, and the upper limit thereof may be about 1,000,000,000 g / mol, 900,000,000 g / mol, The molecular weight may be about 800,000,000 / mol, 700,000,000 / mol, 600,000,000 / mol, 500,000,000 / mol, 400,000,000 / mol, 300,000,000 / mol, 200,000,000 / mol, 150,000,000 / mol, 100,000,000 / mol, 90,000,000 / mol, 80,000,000 / mol, 70,000,000 / mol, or 60,000,000 / mol. The molecular weight may be less than or equal to, or less than any one of the above upper limits; in a range greater than or equal to, or greater than any one of the above lower limits; or in a range less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits.When exposed to heat or flame, starch having the above molecular weight (Mw) can more effectively form a carbide having a desired function (eg, a heat insulating function).

[0052] The lower limit of the weight ratio of the carbonizable organic material to 100 parts by weight of the solvent may be about 0.5 parts by weight, 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 9.5 parts by weight, or about 10 parts by weight, and the upper limit thereof may be about 30 parts by weight, 29 parts by weight, 28 parts by weight, 27 parts by weight, 26 parts by weight, 25 parts by weight, 24 parts by weight, 23 parts by weight, 22 parts by weight, 21 parts by weight, 20 parts by weight, 19 parts by weight, 18 parts by weight, 17 parts by weight, 16 parts by weight, 15 parts by weight, 14 parts by weight, 13 parts by weight, 12 parts by weight, 11 parts by weight, or about 10 parts by weight. The ratio may be in the range of less than or equal to, or less than any of the above upper limits; in the range of greater than or equal to, or greater than any of the above lower limits; or in the range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. The carbonizable organic material contained in such a ratio can efficiently form carbides in the composition as needed, and can ensure excellent handleability and storage stability of the composition as a whole.

[0053] The composition may include a carbonization catalyst generator as another component for ensuring a proper fire extinguishing function. For example, the composition may include a carbonization catalyst generator and a carbonizable organic material. The combination of the above components allows the carbonization of the carbonizable organic material to be more effectively formed at a necessary time point (i.e., when it is necessary to respond to abnormal heating, ignition and / or explosion). For example, a carbonization catalyst generator can promote the carbonization of the carbonizable organic material. The carbonization catalyst generator forms an acid, or an acid-based salt or ion at high temperature, and these components can be used to promote the carbonization. In addition, according to the type of the carbonization catalyst generator, the carbide can be given flame retardancy, or a component that exhibits flame retardancy alone can be formed. For example, the carbonization catalyst generator described below forms a phosphoric acid-based material by decomposing at high temperature, etc., and the material can be polymerized to have flame retardancy. Therefore, the carbonization catalyst generator can be included in the composition so that the composition can respond to abnormal heating, ignition and / or explosion.

[0054] The carbonization catalyst generator needs to be applied by being dispersed in a solvent together with the carbonizable organic material, wherein a carbonization catalyst generator having a solubility higher than a certain level in the solvent (e.g., water) must be used as the carbonization catalyst generator. That is, the components dispersed in the solvent can more effectively contact and interact with each other at the necessary time point to effectively form the desired carbide, etc. In addition, by controlling the solubility of the carbonization catalyst generator in the solvent, agglomeration or phase separation of the components in the composition does not occur, and the above-mentioned carbide formation and / or flame retardant formation can also be more effectively performed. For example, the lower limit of the solubility of the carbonized catalyst generator in the solvent may be about 5g, 10g, 15g, 20g, 25g, 30g, 35g, or 40g, and the upper limit thereof may be about 1000g, 900g, 800g, 700g, 600g, 500g, 400g, 300g, 200g, 100g, 90g, 80g, 70g, 60g, 50g, 40g, or 30g. The solubility may be in a range greater than or equal to, or greater than any of the above lower limits; or in a range less than or equal to, or less than any of the above upper limits, and greater than or equal to, or greater than any of the above lower limits. The solubility is the weight (g) of the carbonized catalyst generator that can be dissolved in 100g of solvent (e.g., water) at 25°C at maximum. The solubility is measured by the method described in "15. Solubility Evaluation" of the Example section of this specification.

[0055] The carbonization catalyst generator can be used without particular limitation, as long as it can be decomposed at high temperature to form an acid or an acid-based salt or ion, etc., and has the above solubility. Examples of carbonization catalyst generators include phosphoric acid compounds such as phosphoric acid and phosphates, phosphonate compounds, or phosphate compounds. The carbonization catalyst generator can be, for example, monoammonium phosphate or diammonium phosphate, urea phosphate, guanyl phosphate urea, or ammonium polyphosphate, etc., and one or two or more of the foregoing can be selected and used.

[0056] Considering the expected effect, the carbonization catalyst generator can be present in the composition in an appropriate amount. For example, the lower limit of the weight ratio of the carbonization catalyst generator relative to 100 weight parts of solvents can be 0.5 weight part, 1 weight part, 5 weight parts, 7 weight parts, 10 weight parts, 11 weight parts, 12 weight parts, 13 weight parts, 14 weight parts, 15 weight parts, 16 weight parts, 17 weight parts, 18 weight parts, 20 weight parts, 25 weight parts, 30 weight parts, 35 weight parts or 38 weight parts, and its upper limit can be 100 weight parts, 95 weight parts, 90 weight parts, 85 weight parts, 80 weight parts, 75 weight parts, 70 weight parts, 65 weight parts, 60 weight parts, 55 weight parts, 50 weight parts, 45 weight parts, 40 weight parts, 35 weight parts, 30 weight parts, 25 weight parts, 20 weight parts, 15 weight parts or 10 weight parts. The ratio may be in a range of less than or equal to, or less than any of the above upper limits; in a range of greater than or equal to, or greater than any of the above lower limits; or in a range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. If the content of the carbonization catalyst generator having excellent solubility in the solvent is too high, the amount of solvent applicable to the composition is limited, and the evaporation characteristics of the solvent are affected by the carbonization catalyst generator dissolved in the solvent, thereby making it difficult to ensure the desired latent heat, so that the amount of the carbonization catalyst generator may be adjusted in consideration of this problem.

[0057] If desired, the composition may include a gas generating material as an optional ingredient. A gas generating material is a material that generates gas when exposed to heat or flame. The gas thus generated can act to directly extinguish the heat or flame, and can also function to make the carbide more porous during the formation of the carbide by the carbonizable organic material.

[0058] The type of gas generated by the gas generating material is not particularly limited as long as it is a non-combustible gas, and may be, for example, nitrogen, carbon dioxide, and / or water vapor.

[0059] Various materials that generate gas are known. For example, materials that generate nitrogen can be exemplified by melamine, guanidine, urea, melamine pyrophosphate, dicyandiamide, guanyl phosphate urea, and glycine, etc.; materials that generate carbon dioxide can be exemplified by potassium bicarbonate, sodium bicarbonate, calcium bicarbonate, and magnesium bicarbonate, etc.; and materials that generate water vapor can be exemplified by calcium hydroxide, magnesium hydroxide, and aluminum hydroxide, etc., but the materials applicable to the present application are not limited thereto. Among the above-mentioned carbonization catalyst generators, there are materials that can generate gas when exposed to high temperatures.

[0060] As the gas generating material, one or a mixture of two or more selected from the above-mentioned types may be used.

[0061] When included, the weight ratio of the gas generating material to 100 parts by weight of the solvent may have a lower limit of about 0.5 parts by weight, 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 9.5 parts by weight, 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight, or 40 parts by weight, and an upper limit thereof may be about 100 parts by weight, 95 parts by weight, 90 parts by weight, 85 parts by weight, 80 parts by weight, 75 parts by weight, 70 parts by weight, 65 parts by weight, 60 parts by weight, 55 parts by weight, 50 parts by weight, 45 parts by weight, 40 parts by weight, or 35 parts by weight. The ratio may be in the range of less than or equal to, or less than any of the above upper limits; in the range of greater than or equal to, or greater than any of the above lower limits; or in the range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. The gas generating material contained in such a ratio can exert an effective suppressing effect on heat or flame and a forming effect of porous carbide in the composition as required, and can ensure excellent handleability and storage stability of the composition as a whole.

[0062] As described above, in appropriate examples, the composition may include both a carbonizable organic material and a gas generating material. In this case, the lower limit of the ratio (G / C) of the weight (G) of the gas generating material to the weight (C) of the carbonizable organic material may be, for example, about 0.5, 1, 1.5, 2, 2.5, 3, 3.5, or 4, and the upper limit thereof may be about 20, 19, 18, 17, 16, 15, 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, or 4. The ratio may be in the range of less than or equal to, or less than any one of the above upper limits; in the range of greater than or equal to, or greater than any one of the above lower limits; or in the range of less than or equal to, or less than any one of the above upper limits, and greater than or equal to, or greater than any one of the above lower limits. The gas generating material and the carbonizable organic material included in such a ratio may exert an effective suppression effect on heat or flame and a formation effect of porous carbides in the composition as required, and may ensure that the composition as a whole has excellent operability and storage stability.

[0063] The composition includes the above ingredients, and may include additional ingredients if necessary.

[0064] For example, the composition may also include a freezing point regulator. As mentioned above, in order for the composition to perform a fire extinguishing function, it is advantageous for the solvent, etc. to be in a liquid phase at a time point when heat, fire and / or explosion that must be controlled occurs. However, depending on the application, the environment in which the composition is placed may be at a temperature below the freezing point of the composition or the solvent, in which case there is a high probability that the composition does not exist in a liquid phase. Therefore, in this case, it is necessary to adjust the freezing point of the composition by adding an appropriate freezing point regulator.

[0065] The type of freezing point adjuster suitable for use in this process is not particularly limited, and additives known to be capable of controlling the freezing point of a solvent or a composition by a so-called freezing point depression phenomenon may be used.

[0066] For example, alcohols may be used as freezing point modifiers.

[0067] For example, as alcohol, an alcohol having a boiling point within a predetermined range can be used. For example, the lower limit of the boiling point of the alcohol may be about 150° C., 170° C., or 190° C., and the upper limit thereof may be about 300° C., 280° C., 260° C., 240° C., 220° C., or 200° C. The boiling point may be within a range less than or equal to, or less than any of the above upper limits; within a range greater than or equal to, or greater than any of the above lower limits; or within a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.

[0068] For example, as alcohol, alcohol with a molar mass within a predetermined range can be used. For example, the lower limit of the molar mass of alcohol can be about 20g / mol, 30g / mol, 40g / mol, 50g / mol, 60g / mol, 70g / mol, 80g / mol, or 90g / mol, and the upper limit can be about 300g / mol, 280g / mol, 260g / mol, 240g / mol, 220g / mol, 200g / mol, 180g / mol, 160g / mol, 140g / mol, 120g / mol, 100g / mol, 90g / mol, 80g / mol, or 70g / mol. The molar mass can be less than or equal to or less than any one of the above upper limits; in a range greater than or equal to or greater than any one of the above lower limits; or in a range less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits.

[0069] The type of alcohol that can be used is not particularly limited, and for example, a monohydric alcohol such as methanol or propylene glycol methyl ether, a diol such as ethylene glycol or propylene glycol, or a polyhydric alcohol such as glycerin can be used.

[0070] If applicable, alcohol may be present so that the concentration calculated based on the solvent is within a predetermined range. The concentration at this time is a molar concentration, which can be specifically obtained by dividing the mole number of the alcohol applied to the composition by the weight (unit: kg) of the solvent. In an example, the lower limit of the molar concentration can be about 2, 4, 6, 8, 10, 12, 14 or 16, and its upper limit can be about 50, 48, 46, 44, 42, 40, 38, 36, 34, 32, 30, 28, 26, 24, 22 or 20. The molar concentration can be less than or equal to or less than the above-mentioned upper limit in the range of any one; in the range of greater than or equal to or greater than the above-mentioned lower limit; or in the range of less than or equal to or less than the above-mentioned upper limit, while greater than or equal to or greater than the above-mentioned lower limit in the range of any one. However, the desired freezing point range can be considered to adjust the molar concentration.

[0071] Such compositions can exhibit unique physical properties through the combination of the above components.

[0072] For example, the composition can exhibit a fully controlled freezing point. For example, the lower limit of the freezing point of the composition can be about -50°C, -45°C, -40°C, -35°C, -30°C, -25°C, -20°C, -15°C, or -10°C, and the upper limit thereof can be about 10°C, 8°C, 6°C, 4°C, 2°C, 0°C, -5°C, -10°C, -15°C, -20°C, -25°C, -30°C, -35°C, or -40°C. The freezing point can be within a range of less than or equal to, or less than any of the above upper limits; within a range of greater than or equal to, or greater than any of the above lower limits; or within a range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. Such a freezing point can be measured by the method described in "2. Freezing Point Measurement" of the Examples section.

[0073] The composition may have a controlled viscosity and / or thixotropic index.

[0074] For example, the lower limit of the viscosity of the composition may be 30,000 cP, 40,000 cP, 50,000 cP, 60,000 cP, 70,000 cP, 80,000 cP, 90,000 cP, 100,000 cP, 110,000 cP, 120,000 cP, 130,000 cP, 140,000 cP, 150,000 cP, or 155,000 cP. Right, and its upper limit can be 600,000cP, 550,000cP, 500,000cP, 450,000cP, 400,000cP, 350,000cP, 300,000cP, 250,000cP, 200,000cP, 150,000cP, 100,000cP, 90,000cP, 80,000cP, or 70,000cP or so. The viscosity can be less than or equal to, or less than any one of the above upper limits; in a range greater than or equal to, or greater than any one of the above lower limits; or in a range less than or equal to, or less than any one of the above upper limits, and greater than or equal to, or greater than any one of the above lower limits. Such viscosity is a value measured at room temperature (about 25° C.) and a rotation speed of 0.5 rpm. The viscosity can be measured by the method described in "1. Measurement of viscosity and thixotropic index" in the Example section of the present specification.

[0075] The lower limit of the thixotropic index of the composition may be about 2, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, or 10.5, and the upper limit thereof may be about 20, 18, 16, 14, 12, 10, 8, or 6. The thixotropic index may be in a range less than or equal to, or less than any of the above upper limits; in a range greater than or equal to, or greater than any of the above lower limits; or in a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. The thixotropic index is a value obtained by dividing the viscosity measured at room temperature (about 25° C.) and a rotation speed of 0.5 rpm by the viscosity measured at room temperature (about 25° C.) and a rotation speed of 5 rpm. The thixotropic index may be measured by the method described in “1. Measurement of viscosity and thixotropic index” of the Examples section of this specification.

[0076] A composition having such a viscosity and / or thixotropic index may exhibit excellent workability, storage stability, and the like.

[0077] Compositions may exhibit certain latent heat properties. Latent heat is generally defined as the amount of heat required for any material to cause a change of state (phase change) without any temperature change. However, when the composition of the present application exhibits latent heat, it does not necessarily have to cause an overall change of state. The latent heat of the present application may be generated in the process of changing the state of at least a portion of the composition or a component included in the composition.

[0078] In the present application, the situation that the composition exhibits latent heat means that in the DSC (differential scanning calorimeter) analysis performed in the manner described in the embodiment to be described below, the composition shows an endothermic peak within a predetermined temperature range. The process in which the composition of the present application exhibits latent heat can be an isothermal process or a similar process. Therefore, the composition can be applied to heat-generating products to control heat while keeping the temperature of the product uniform, and can minimize or prevent the influence of abnormal heating, explosion and / or fire occurring in one product on other adjacent products.

[0079] The lower limit of the latent heat exhibited by the composition can be, for example, about 500 J / g, 550 J / g, 600 J / g, 650 J / g, 700 J / g, 750 J / g, 800 J / g, 850 J / g, 900 J / g, 950 J / g, 1000 J / g, 1100 J / g, 1200 J / g, or 1300 J / g, and the upper limit thereof can be about 3000 J / g, 2800 J / g, 2600 J / g, 2400 J / g, 2200 J / g, 2000 J / g, 1800 J / g, 1600 J / g, 1400 J / g, 1200 J / g, 1000 J / g, or 900 J / g. The latent heat may be in a range greater than or equal to, or greater than any of the above lower limits; or in a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. The latent heat may be determined by the method described in "7. Measurement of latent heat" of the Examples section of this specification.

[0080] The lower limit of the range of the starting temperature at which the composition begins to express latent heat may be, for example, about 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, or 95°C, and the upper limit thereof may be about 200°C, 180°C, 160°C, 140°C, 120°C, 100°C, 90°C, or 80°C. The starting temperature may be determined in the range of greater than or equal to, or greater than any one of the above lower limits while less than or equal to, or less than any one of the above upper limits. The starting temperature means the temperature at the left starting point of the endothermic peak section determined by the method described in "7. Measurement of latent heat" of the Example section in this specification.

[0081] The lower limit of the temperature section representing the latent heat of the composition may be, for example, about 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, or 180°C, and the upper limit thereof may be about 300°C, 280°C, 260°C, 240°C, 220°C, 200°C, 180°C, or 160°C. The temperature section range may be determined within a range that is greater than or equal to, or greater than any of the above lower limits while being less than or equal to, or less than any of the above upper limits. The temperature section is a value obtained by subtracting the temperature of the left starting point from the temperature of the right starting point of the endothermic peak section determined by the method described in "7. Measurement of latent heat" of the Example section in this specification.

[0082] Through the above characteristics, the composition can be applied to various applications to effectively respond to heat generation, fire and / or explosion occurring in the corresponding applications.

[0083] The freezing point, viscosity, thixotropic index and latent heat characteristics of the composition as described above can be ensured by the combination of the components of each composition as described above.

[0084] Furthermore, the composition may further contain various types of known additives as long as the above-mentioned physical properties are not impaired.

[0085] The present application also relates to a fire extinguishing assembly manufactured using the composition. Considering the storage ease and operational stability of the composition, the fire extinguishing assembly can be manufactured by loading the composition into a suitable housing.

[0086] Thus, a fire extinguishing assembly may include: a housing; and a composition present in the housing.

[0087] The type of housing used to manufacture the fire extinguishing assembly is not particularly limited, as long as it can properly store the composition, it can be used. The composition contains a volatile component such as a solvent, so that in one example, a housing having a so-called WVTR (Water Vapor Transmission Rate) within a predetermined range can be used as the housing.

[0088] For example, the upper limit of the so-called WVTR (water vapor transmission rate) of the above housing may be 0.5 g / m 2 Day, 0.45g / m 2 Day, 0.4g / m 2 Day, 0.35g / m 2 Day, 0.3g / m 2 Day, 0.25g / m 2 Day, 0.2g / m2 Day, 0.15g / m 2 ·day, or 0.1g / m 2 · days, and its lower limit can be 0g / m 2 Day, 0.1g / m 2 Day, 0.2g / m 2 Day, 0.3g / m 2 Day, 0.4g / m 2 ·day, or 0.5g / m 2 · days. The WVTR may be in the range of less than or equal to, or less than any of the above upper limits; in the range of greater than or equal to, or greater than any of the above lower limits; or in the range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. The WVTR may be determined by the method described in "12. WVTR (water vapor transmission rate) evaluation" in the Examples section of this specification.

[0089] Such a housing can be manufactured using various known materials. For example, the housing can be constructed using an appropriate inorganic film and / or organic film, or can be constructed by laminating them.

[0090] Here, applicable organic films can be exemplified as cellulose-based polymer films; COP (cyclic olefin copolymer) films; acrylic polymer films; polyolefin films; PVA (polyvinyl alcohol) films; PES (polyethersulfone) films; PEEK (polyetheretherketone) films; PPS (polyphenylsulfone) films; PEI (polyetherimide) films; PEN (polyethylene naphthalate) films; polyester films; PI (polyimide) films; polysulfone (PSF) films; and / or PAR (polyarylate) films; and the like.

[0091] Here, the applicable inorganic film can be exemplified as a metal film, a metal oxide film, a metal nitride film, or a metal oxynitride film, etc. For example, a metal film, a metal oxide film, a metal nitride film, or a metal oxynitride film containing one or more selected from In, Sn, Pb, Au, Cu, Ag, Zr, Hf, Zn, Al, Si, La, Ti and Ni can be used.

[0092] By selecting appropriate types of these films and combining them as required, a desired type of housing can be provided.

[0093] Here, the form of the housing or the fire extinguishing assembly is determined according to the intended use, and is not particularly limited.

[0094] For example, as described below, when the fire extinguishing assembly is applied to a battery module and applied between a plurality of battery cells included in the module, the fire extinguishing assembly can be manufactured by making the shape of the case the same as or similar to the battery cell and then inserting it between the battery cells.

[0095] The specification also discloses an electronic device or apparatus using the composition or the fire extinguishing assembly.

[0096] The type of electronic equipment or device is not particularly limited. For example, the composition or fire extinguishing assembly can be applied to equipment or devices in which there is a risk of abnormal heating, fire and / or explosion during driving, maintenance and / or storage, and the related abnormal phenomena must be controlled.

[0097] Examples of the above devices or apparatuses include batteries. In particular, in a battery module constructed using a plurality of battery cells, it is important to prevent abnormal heating, fire, and / or explosion occurring in one battery cell from spreading to other adjacent battery cells.

[0098] Thus, the present application may relate to a battery module comprising the composition or the fire extinguishing assembly.

[0099] Such a battery module may basically include a plurality of battery cells; and a combination or fire extinguishing assembly disposed between the battery cells.

[0100] If the composition or fire extinguishing assembly is applied, the specific configuration of the battery module (eg, the type of battery cell, etc.) is not particularly limited, and known materials may be applied. For example, known pouch-shaped, rectangular or cylindrical battery cells may be used as battery cells.

[0101] The manufacturing method of the battery module is not particularly limited, for example, as described above, a method of manufacturing a fire extinguishing assembly in the form of a battery cell and then placing the fire extinguishing assembly at a desired position during the manufacturing process of the battery module may be used.

[0102] Beneficial Effects

[0103] This specification discloses a product or element that is applied to generate heat or has a possibility of catching fire or exploding during a driving, storage and / or maintenance process, so that a composition that can effectively respond to heat, catching fire and exploding can be used. For example, the composition is applied to an article comprising a plurality of products or elements, so that it can respond to abnormal heating, explosion and catching fire that occur in any one element or product, and prevent or minimize the propagation of such heating, explosion and catching fire to other adjacent elements or products. The composition also shows excellent operability and storage stability. This specification can also provide the purposes of the composition. DETAILED DESCRIPTION

[0104] Hereinafter, the composition disclosed herein will be described in more detail with reference to Examples and Comparative Examples, but the scope of the composition is not limited to the following Examples.

[0105] 1. Measurement of viscosity and thixotropic index

[0106] The viscosity was evaluated at about 25°C using a viscosity measuring device (Brookfield viscometer, RV model). The viscosity was measured at 25°C using a spindle #63 while changing the rotation speed (shear rate) in the range of 0.5 rpm to 5 rpm. The sample (composition) was loaded into the viscosity measuring device, and the rotation speed was maintained at each rotation speed for about 1 minute to stabilize the viscosity, and then the viscosity was measured. Thixotropic index (V 0.5 The viscosity at a rotation speed of 0.5 rpm (V5) is obtained by dividing the viscosity measured in the above manner by the viscosity at a rotation speed of 0.5 rpm (V 0.5 ) divided by the viscosity (V5) at a rotation speed of 5 rpm.

[0107] 2. Freezing point measurement

[0108] The freezing point was evaluated by the method specified in the OECD Guideline for testing of chemicals 102 (adopted by the Council on July 27, 1995).

[0109] 3. Convection test

[0110] Composition is loaded into the aluminum tray that bottom thickness is about 0.2mm.Load so that the thickness of composition is about 3mm.Aluminum tray is placed on temperature sensor (k type thermocouple), and at the height of about 1 inch of composition loaded on the tray, flame is applied vertically towards composition.Use butane gas and blowtorch to apply flame.Measure temperature with temperature sensor while applying flame about 3 minutes, and it is evaluated according to the following standard.

[0111] <Evaluation Criteria>

[0112] PASS: When the measured temperature of the temperature sensor remains below 300°C

[0113] NG: When the temperature sensor measures a temperature higher than 300°C, or the aluminum plate is observed to be melted

[0114] 4. Formation of carbides (porous carbides, foams)

[0115] After the convection test, the position where the composition was loaded was observed and evaluated according to the following criteria.

[0116] <Evaluation Criteria>

[0117] PASS: When the aluminum disk is not damaged and carbides are confirmed at the location of the composition

[0118] NG: When the aluminum plate is damaged or confirmed to have no carbide

[0119] 5. Chain fire test

[0120] The rectangular batteries are arranged side by side at intervals of about 3 mm, and an assembly (fire extinguishing assembly) containing the composition is placed therebetween. As a rectangular battery, a product of CATL (120Ah, 3.2V, size = thickness × width × width = 48 × 174 × 165) is used, and it is applied to the test at 100% charge state. In the above arrangement, according to the SAE J2464:2009 standard, a battery fire is initiated in one rectangular battery, and a chain fire in another battery cell is checked. The battery fire is initiated by piercing a nail with a diameter of about 5 mm into the rectangular battery at a speed of 25 mm / second (Nail Penetration method).

[0121] <Evaluation Criteria>

[0122] PASS: When no fire occurs in the battery cells other than the one punctured by the nail

[0123] NG: When a fire occurs in a battery cell other than the battery cell punctured by the nail

[0124] 6. Storage stability evaluation

[0125] The fire extinguishing assembly was stored in an oven at a temperature of about 35° C. for 1,000 hours, and the weight change before and after storage in the oven was measured. When the weight change before and after storage was 1% or more, it was evaluated as NG, and when the weight change was less than 1% or there was no weight change, it was evaluated as PASS.

[0126] 7. Measurement of latent heat

[0127] The latent heat is evaluated in the following manner. Each composition of the embodiment or comparative example is collected in an amount of about 3 mg to 5 mg or so and loaded into a measuring device. As a measuring device, a DSC (differential scanning calorimeter) device (TA Instruments, Q200 type) is used. When evaluating the latent heat, the temperature section is set to 25°C to 300°C. While the temperature is raised from 25°C to 300°C at a rate of about 20°C / min and the isothermal section is kept for about 15 minutes, the endothermic peak is measured. The left starting point and the right starting point of the endothermic peak section are designated as the starting point and end point of the endothermic peak, and the latent heat (unit: J / g) is calculated by integrating the relevant sections.

[0128] 8.CRC (centrifugal retention capacity)

[0129] CRC was measured according to EDANA WSP 241.3. About 0.2 g (W0) of water-absorbent polymer was placed in a nonwoven encapsulant, sealed, and then immersed in a physiological saline solution at room temperature. As the physiological saline solution, a 0.9 wt % NaCl aqueous solution was used. This state was maintained for about 30 minutes, and water was removed from the encapsulant using a centrifuge at 250 G for 3 minutes, and then the mass of the encapsulant was measured (g, W2).

[0130] The same operation was performed on the same nonwoven wrapper without any water-absorbing polymer, and the mass (g, W1) was measured.

[0131] CRC(g / g) is calculated by substituting the measurement result into the following equation A.

[0132] The evaluation was performed under constant temperature and humidity conditions (23±1° C., relative humidity: 50±10%).

[0133] [Equation A]

[0134] CRC(g / g)={[W2(g)-W1(g)] / W0(g)}-1

[0135] 9.AUP (Absorption Percentage Under Pressure)

[0136] AUP was measured according to EDANA method WSP 242.3. A 400 mesh stainless steel wire mesh was mounted on the bottom of a plastic cylinder with an inner diameter of about 60 mm, and 0.0 g (W0) (0.90 g) of water-absorbing polymer was evenly sprayed on the wire mesh, and then a piston capable of evenly imparting a 0.3 psi load was mounted thereon. The piston was slightly smaller than the outer diameter of 60 mm, had no gap with the inner wall of the cylinder, and was mounted so that it could move up and down. The weight of the device was measured (g, W3).

[0137] A glass filter having a diameter and thickness of 90 mm and 5 mm, respectively, was placed in a culture dish having a diameter of 150 mm, and a physiological saline solution was added so that it was at the same level as the upper surface of the glass filter. As the physiological saline solution, a NaCl aqueous solution having a concentration of 0.9 wt % was used. A filter paper having a diameter of 90 mm was placed thereon. A measuring device was placed on the filter paper and the physiological saline solution was absorbed under a load of 0.3 psi for 1 hour. Thereafter, the measuring device was raised and its weight (g, W4) was measured.

[0138] AUP (g / g) was estimated by substituting the obtained value into the following equation B.

[0139] The evaluation was performed under constant temperature and humidity conditions (23±1° C., relative humidity: 50±10%).

[0140] [Equation B]

[0141] AUP (g / g) = [W4 (g) - W3 (g)] / W0 (g) 10. Molecular weight measurement

[0142] The molecular weight of starch was evaluated in the following manner.

[0143] (1) Preparation of mobile phase

[0144] Mobile phase A was prepared by filtering 1000 mL of a 150 mM NaNO 3 aqueous solution containing 0.02 wt % NaN 3 using a solvent purification system (Millipore Millisolve Kit, MilliporeSigma).

[0145] (2) Preparation of sample solution

[0146] A sample to be measured was collected in an amount of 25 mg and mixed with 5 mL of a 150 mM NaNO 3 aqueous solution containing 0.02 wt % NaN 3 , and then a sample solution was prepared by heating the mixture at 80° C. for 20 hours and then filtering it with a 0.4 μm nylon syringe filter.

[0147] (3) GPC (Gel Permeation Chromatography) / MALS (Multi-Angle Light Scattering) Conditions The molecular weight was evaluated using the sample solution and the mobile phase A in the following manner.

[0148] Measuring instrument: Agilent GPC (Agilent 1200 series, USA)

[0149] Stationary phase: connected to Shodex OH-Pak 804 column and Shodex OH-Pak 80 column Mobile phase: A; 0.02% NaN3, 150mM NaNO3 aqueous solution = 100 (volume / volume%)

[0150] Flow rate: 0.4mL / min

[0151] Stationary phase temperature: 25°C

[0152] Injection volume: 100 μl (0.45 μm filtered)

[0153] Analysis time: 120 minutes

[0154] 11. Measurement of Amylopectin and Amylose Content

[0155] The amylopectin and amylose contents in starch were evaluated according to the method described in the paper (Potato Research 31 (1988) 241-246).

[0156] First, the sample was prepared by dissolving about 5 mg of starch in about 1 mL of sterile water (step 1), and heated to 95°C in a constant temperature water bath for about 15 minutes (step 2).

[0157] Subsequently, about 20 μl of the sample was placed in a cuvette (step 3), and about 980 μl of the iodine solution was added thereto and mixed (step 4).

[0158] Subsequently, the absorbance of the sample mixed with the iodine solution at wavelengths of 525 nm and 700 nm was measured and recorded (step 5). The absorbance was measured using the OPTIZEN POP model of KLAB.

[0159] About 20 μl of water is placed in another cuvette, 980 μl of iodine solution is added thereto, and mixed (step 6). For the solution of step 6, the absorbance at wavelengths of 525 nm and 700 nm is measured and recorded in the same manner as in step 5 (step 7).

[0160] The absorbance obtained in step 7 is subtracted from the absorbance obtained in step 5, and the ratio (%) of amylose is determined according to the following equation C (step 8).

[0161] [Equation C]

[0162]

[0163] In equation C, PA is the ratio of amylose (%), OD is 700 is the value obtained by subtracting the absorbance at a wavelength of 700 nm measured in step 7 from the absorbance at a wavelength of 700 nm measured in step 5, and OD 525 is a value obtained by subtracting the absorbance at a wavelength of 525 nm measured in step 7 from the absorbance at a wavelength of 525 nm measured in step 5.

[0164] 12.WVTR (water vapor transmission rate) evaluation

[0165] The WVTR of the outer shell used to make the fire extinguishing assembly housing was evaluated according to ASTM F1249 standard at 38°C and 100% relative humidity.

[0166] 13. Processability assessment

[0167] The processability was evaluated by dispensing each composition prepared in the examples or comparative examples using a dispensing device and then checking whether there was fluidity at the time point when the dispensing pressure was removed. When there was no fluidity, it was evaluated as PASS, and when there was fluidity, it was evaluated as NG.

[0168] 14. Operability Assessment

[0169] The operability was evaluated by evaluating the ease of operation during the process of inserting the manufactured fire extinguishing assembly between battery cells and the process of transporting the fire extinguishing assembly, and also observing whether phase separation occurred in the composition.

[0170] If both of the following ease of operation and the absence of phase separation were PASS, the final operability evaluation result was set to PASS, and if either one of them was NG, the final operability evaluation result was set to NG.

[0171] <Ease of operation evaluation criteria>

[0172] PASS: When during the process of inserting the fire extinguishing assembly between battery cells, the fire extinguishing assembly does not bend or sag, and the composition inside the fire extinguishing assembly does not tilt in one direction, and during the process of transporting the fire extinguishing assembly by a robot arm or a worker with both hands, the fire extinguishing assembly does not bend or sag, and the original shape of the fire extinguishing assembly is well maintained

[0173] NG: When any of the following occurs: a case where the fire extinguishing assembly is bent or drooped during the process of inserting the fire extinguishing assembly between battery cells; a case where the automation process cannot be smoothly performed due to the composition inside the fire extinguishing assembly being tilted in one direction; and a case where the fire extinguishing assembly is bent or drooped during the process of transporting the fire extinguishing assembly by a robot arm or a worker with both hands, and thus cannot well maintain its original shape

[0174] <No phase separation>

[0175] PASS: When the composition is kept in a 20L tank container at room temperature (about 25°C) for 24 hours, the upper and lower layers of the tank are uniform and no separated phases are observed.

[0176] NG: When the composition was kept in a 20 L tank container at room temperature (about 25°C) for 24 hours, the upper and lower layers of the tank were not uniform, and separated phases were observed.

[0177] 15. Solubility Assessment

[0178] The solubility of the materials was evaluated based on the ASTM E1148-02 standard. According to the above standard, the solubility was determined by evaluating the amount that dissolved at most in 100 g of water at room temperature (about 25°C).

[0179] 16. Evaluation of gelatinization viscosity

[0180] The gelatinization viscosity of starch was evaluated using an Amylograph-E (Brabender) device. About 58 g of starch was dissolved in 450 mL of distilled water. The following process was performed: the temperature of the distilled water in which the starch was dissolved was raised from 35°C to 95°C at a rate of 1.5°C / min, the temperature was maintained at 95°C for 15 minutes, and then the temperature was reduced from 95°C to 50°C at a rate of 1.5°C / min. In the above process, the peak that appeared while the swelling structure of the starch collapsed was determined, and the viscosity value of the peak was used as the gelatinization viscosity of the starch.

[0181] 17. Weight-based size distribution of water-absorbent polymers

[0182] The weight-based size distribution of water-absorbent polymers is measured according to EDANA WSP 220.3. According to the above standard, a stainless steel sieve (diameter: about 200 mm) with a hole size of 150 μm, 300 μm, 600 μm and 850 μm is used to obtain a weight-based size distribution. Using the standard and the sieve, the water-absorbent polymer sample is classified based on the particle size, and the weight of the corresponding classified particles is expressed as a percentage. Specifically, the sample is divided into a particle size less than 150 μm, a particle size in the range of 150 μm to 300 μm, a particle size in the range of 300 μm to 600 μm, a particle size in the range of 600 μm to 850 μm, and a particle size greater than 850 μm, and the percentage relative to the weight of the entire sample is determined by measuring the weight of each particle size.

[0183] Example 1.

[0184] Preparation of composition

[0185] Water (tap water) (W), ethylene glycol (E), ammonium phosphate (N) ((NH4)3PO4) and starch (S) are mixed in a weight ratio (W:E:N:S) of 100:100:40:10 to prepare a mixture. The mixing is performed at room temperature (about 25°C) for about 10 minutes under a mixing condition of 500rpm. As starch, corn starch is used, wherein the weight average molecular weight of the starch is about 51,000,000 g / mol, the weight ratio of amylose to amylopectin in the starch (amylose: amylopectin) is about 26:74, and the gelatinization viscosity of the starch is about 260BU (Brabender unit). The solubility of ammonium phosphate (N) (NH4H2PO4) in water at 25°C is about 29g.

[0186] Subsequently, a composition is prepared by further mixing a water-absorbent polymer (SAP) into the mixture. The mixing of the water-absorbent polymer is performed by mixing the mixture with the water-absorbent polymer and mixing the mixture at room temperature (about 25° C.) under a mixing condition of 500 rpm for about 2 hours.

[0187] Mixing is performed so that the weight ratio of water to water-absorbent polymer (SAP) in the mixture (water: SAP) is about 100:8. As the water-absorbent polymer, LG Chemical's GS-803ND product is used. The CRC (centrifuge retention capacity) of the water-absorbent polymer is about 33.5 g / g, and the AUP (absorption rate under pressure) is about 28.1 g / g. In addition, in the size distribution based on weight, the ratio of the particle size less than 150 μm is about 1.5 weight%, the ratio of the particle size in the range of 150 μm to 300 μm is 20.5 weight%, the ratio of the particle size in the range of 300 μm to 600 μm is 74.6 weight%, the ratio of the particle size in the range of 600 μm to 850 μm is 3.4 weight%, and the ratio of the particle size greater than 850 μm is 0 weight%. Therefore, in the weight-based size distribution of the water-absorbent polymer, the maximum weight size was 300 μm to 600 μm, and the weight ratio of the water-absorbent polymer belonging to the maximum weight size was 74.6 wt %.

[0188] Manufacture of fire extinguishing assemblies

[0189] The composition was introduced into a shell to manufacture a fire extinguishing assembly. The shell was manufactured using a shell in which a PET (poly(ethylene terephthalate)) film (thickness: about 10 μm), a PVDC (poly(vinylidene chloride)) film (thickness: about 40 μm) and a PP (polypropylene) film (thickness: about 50 μm) were laminated in this order. The shell was manufactured by laminating a PET film on one side of the PVDC film with an adhesive and a PP film on the other side at a temperature of about 200° C. The WVTR of the shell was about 0.11 g / m 2 · days or so. The shell is manufactured using this shell. At this time, the shell is manufactured in the form of a rectangular battery cell shell (thickness is about 3 mm). The composition prepared above is introduced into the shell, and the shell is sealed to manufacture a fire extinguishing assembly.

[0190] Example 2.

[0191] Preparation of composition

[0192] Water (tap water) (W), ethylene glycol (E), potassium bicarbonate (K) (KHCO3) and starch (S) are mixed in a weight ratio (W:E:K:S) of 100:100:33.3:10 to prepare a mixture. Mixing is performed at room temperature (about 25°C) for about 10 minutes under a mixing condition of 500rpm. As starch, the starch used in Example 1 is used. Subsequently, a composition is prepared by further mixing a water-absorbent polymer (SAP) into the mixture. The mixing of the water-absorbent polymer is performed by mixing the mixture with the water-absorbent polymer and mixing the mixture at room temperature (about 25°C) under a mixing condition of 500rpm for about 2 hours. Mixing is performed so that the weight ratio (water:SAP) of water to the water-absorbent polymer (SAP) in the mixture is about 100:9, and the same water-absorbent polymer as used in Example 1 is applied as the water-absorbent polymer.

[0193] Manufacture of fire extinguishing assemblies

[0194] The composition prepared above was introduced into a housing to manufacture a fire extinguishing assembly. The housing was manufactured using a housing in which a PET (poly (ethylene terephthalate)) film (thickness: about 10 μm), an aluminum foil (thickness: about 20 μm) and a PP (polypropylene) film (thickness: about 70 μm) were laminated in this order. The housing was manufactured by laminating a PET film on one side of the aluminum foil with an adhesive and a PP film on the other side at a temperature of about 200° C. The WVTR of the housing was about 0 g / m 2 · days or so. The shell is manufactured using this shell. At this time, the shell is manufactured in the form of a rectangular battery cell shell (thickness is about 3 mm). The composition prepared above is introduced into the shell, and the shell is sealed to manufacture a fire extinguishing assembly.

[0195] Example 3.

[0196] Preparation of composition

[0197] Water (tap water) (W), ethylene glycol (E), ammonium phosphate (N) ((NH4)3PO4), starch (S) and hollow filler (HF) are mixed in a weight ratio (W:E:N:S:HF) of 100:60:40:10:5 to prepare a mixture. The mixing is carried out at room temperature (about 25°C) for about 10 minutes under a mixing condition of 500rpm. As starch, the starch used in Example 1 is used, and as a hollow filler, a 3M product (product name: XLD3000, average particle size (D50 particle size): 30μm, density: about 0.23g / ml) is used. The solubility of ammonium phosphate (N) (NH4H2PO4) in water at 25°C is about 29g. Subsequently, a composition is prepared by further mixing a water-absorbent polymer (SAP) into the mixture. The mixing of the water-absorbent polymer is carried out by mixing the mixture with the water-absorbent polymer and mixing the mixture at room temperature (about 25°C) under a mixing condition of 500rpm for about 2 hours. Mixing was performed so that the weight ratio of water to the water-absorbent polymer (SAP) in the mixture (water:SAP) was about 100:7, and the same water-absorbent polymer as used in Example 1 was applied as the water-absorbent polymer.

[0198] Manufacture of fire extinguishing assemblies

[0199] The composition prepared above was introduced into a shell to manufacture a fire extinguishing assembly. The shell was manufactured using a shell in which a PET (poly (ethylene terephthalate)) film (thickness: about 10 μm), an EVOH (ethylene vinyl alcohol copolymer) film (thickness: about 40 μm) and a PE (polyethylene) film (thickness: about 50 μm) were laminated in this order. The shell was manufactured by laminating a PET film on one side of the EVOH film with an adhesive and laminating a PE film on the other side at a temperature of about 200° C. The WVTR of the shell was about 0.27 g / m 2 · days or so. The shell is manufactured using this shell. At this time, the shell is manufactured in the form of a rectangular battery cell shell (thickness is about 3 mm). The composition prepared above is introduced into the shell, and the shell is sealed to manufacture a fire extinguishing assembly.

[0200] Example 4.

[0201] Preparation of composition

[0202] Water (tap water) (W), ammonium phosphate (N) ((NH4)3PO4) and starch (S) are mixed in a weight ratio (W:N:S) of 100:40:10 to prepare a mixture. Mixing is performed at room temperature (about 25°C) for about 10 minutes under a mixing condition of 500rpm. As starch, the starch used in Example 1 is used. The solubility of ammonium phosphate (N) (NH4H2PO4) in water at 25°C is about 29g. Subsequently, a composition is prepared by further mixing a water-absorbent polymer (SAP) into the mixture. The mixing of the water-absorbent polymer is performed by mixing the mixture with the water-absorbent polymer and mixing the mixture at room temperature (about 25°C) under a mixing condition of 500rpm for about 2 hours. Mixing is performed so that the weight ratio of water to the water-absorbent polymer (SAP) in the mixture (water:SAP) is about 100:8, and the same water-absorbent polymer as used in Example 1 is applied as the water-absorbent polymer.

[0203] Manufacture of fire extinguishing assemblies

[0204] The fire extinguishing assembly was manufactured by introducing the composition into the housing used in Example 2.

[0205] Comparative Example 1.

[0206] Preparation of composition

[0207] Water (tap water) (W) and ethylene glycol (EG) are mixed in a weight ratio (W:EG) of 100:100 to prepare a mixture. Mixing is performed at room temperature (about 25°C) for about 10 minutes under a mixing condition of 500rpm. Subsequently, a composition is prepared by further mixing a water-absorbent polymer (SAP) into the mixture. The mixing of the water-absorbent polymer is performed by mixing the mixture with the water-absorbent polymer and mixing the mixture at room temperature (about 25°C) under a mixing condition of 500rpm for about 2 hours. Mixing is performed so that the weight ratio of water to the water-absorbent polymer (SAP) in the mixture (water:SAP) is about 100:10, and the same water-absorbent polymer as used in Example 1 is applied as the water-absorbent polymer.

[0208] Manufacture of fire extinguishing assemblies

[0209] The fire extinguishing assembly was manufactured by introducing the composition into the housing used in Example 2.

[0210] Comparative Example 2.

[0211] Preparation of composition

[0212] Water (tap water) (W), ethylene glycol (E) and ammonium phosphate (N) ((NH4)3PO4) are mixed in a weight ratio (W:E:N) of 100:100:40 to prepare a mixture. Mixing is performed at room temperature (about 25°C) for about 10 minutes under a mixing condition of 500rpm. Subsequently, a composition is prepared by further mixing a water-absorbent polymer (SAP) into the mixture. The mixing of the water-absorbent polymer is performed by mixing the mixture with the water-absorbent polymer and mixing the mixture at room temperature (about 25°C) under a mixing condition of 500rpm for about 2 hours. Mixing is performed so that the weight ratio of water to the water-absorbent polymer (SAP) in the mixture (water:SAP) is about 100:8, and the same water-absorbent polymer as used in Example 1 is applied as the water-absorbent polymer.

[0213] Manufacture of fire extinguishing assemblies

[0214] The fire extinguishing assembly was manufactured by introducing the composition into the housing used in Example 2.

[0215] Comparative Example 3.

[0216] Water (tap water) (W), ethylene glycol (E), ammonium phosphate (N) ((NH4)3PO4) and starch (S) were mixed in a weight ratio (W:E:N:S) of 100:100:40:25 to prepare a mixture. The mixing was performed at room temperature (about 25°C) for about 10 minutes under a mixing condition of 500 rpm. The same starch as in Example 1 was used as the starch. Subsequently, a composition was prepared by further mixing a water-absorbent polymer (SAP) into the mixture. The mixing of the water-absorbent polymer was performed by mixing the mixture with the water-absorbent polymer and mixing the mixture at room temperature (about 25°C) under a mixing condition of 500 rpm for about 2 hours. The mixing was performed so that the weight ratio of water to the water-absorbent polymer (SAP) in the mixture (water:SAP) was about 100:8, and the same water-absorbent polymer as used in Example 1 was applied as the water-absorbent polymer. In the above case, the composition was not properly formed into a gel phase, making it impossible to measure the viscosity and thixotropic index, and the fire extinguishing assembly could not be manufactured.

[0217] Comparative Example 4.

[0218] A composition and a fire extinguishing assembly were prepared in the same manner as in Example 1, except that LG Chemical's MG-2600 product was used as the water-absorbent polymer. The water-absorbent polymer MG-2600 was prepared from the same material as the water-absorbent polymer used in Example 1, but was a water-absorbent polymer in which the ratio of the particle size of less than 150 μm in the weight-based size distribution was 100% by weight.

[0219] The evaluation results of the compositions and fire extinguishing assemblies of the above Examples and Comparative Examples are shown in the following Tables 1 and 2. In Comparative Example 3, a fire extinguishing assembly could not be produced because the composition was not properly formed into a gel phase, and thus could not be evaluated.

[0220] [Table 1]

[0221]

[0222] [Table 2]

[0223]

Claims

1. A composition comprising: a solvent; and Water-absorbing polymer, wherein The ratio of the viscosity at a shear rate of 0.5 rpm and 25° C. to the viscosity at a shear rate of 5 rpm and 25° C. is 4 or more. 2 . The composition according to claim 1 , wherein the viscosity at a shear rate of 0.5 rpm and 25° C. is in the range of 30,000 cP to 600,000 cP.

3. The composition of claim 1, wherein the composition exhibits a latent heat of 500 J / g or greater.

4. The composition according to claim 1, wherein the freezing point of the composition is in the range of -50°C to 10°C.

5. The composition according to claim 1, wherein the freezing point of the solvent is -5°C or higher. The composition according to claim 1 , wherein the solvent is water.

7. The composition according to claim 1, wherein the water-absorbing polymer is particulate, and wherein the water-absorbing polymer exhibits a size distribution in which the maximum weight size in the weight-based size distribution according to EDANA method WSP 220.3 is in the range of 150 μm to 850 μm. 8 . The composition according to claim 7 , wherein a weight ratio of the water-absorbent polymer belonging to the maximum weight size in the weight-based size distribution is 50 weight % or more.

9. The composition of claim 1, wherein the water-absorbing polymer has a centrifuge retention capacity (CRC) according to EDANA method WSP 241.3 of 12 g / g or more.

10. The composition of claim 1, wherein the water-absorbing polymer has an Absorption Under Pressure (AUP) at 0.3 psi according to EDANA method WSP 242.3 of 4 g / g or greater. 11 . The composition according to claim 1 , wherein the water-absorbent polymer is included in an amount of 1 part by weight to 30 parts by weight relative to 100 parts by weight of the solvent.

12. The composition of claim 1, further comprising a carbonizable organic material. 13 . The composition according to claim 12 , wherein the carbonizable organic material has a gelatinization viscosity of 150 BU or more.

14. The composition of claim 12, wherein the carbonizable organic material is a polysaccharide, a polyol, cellulose, lignin, BSPPO, a carbonizable polymer, or a melamine compound. 15 . The composition according to claim 12 , wherein the carbonizable organic material is included in an amount of 1 part by weight to 40 parts by weight relative to 100 parts by weight of the solvent.

16. The composition according to claim 12, further comprising a carbonization catalyst generator. 17 . The composition according to claim 16 , wherein the carbonized catalyst generating agent has a solubility of 5 g or more in 100 g of water at 25° C.

18. A fire extinguishing assembly comprising: case; and A composition according to any one of claims 1 to 17 present in the housing.

19. A battery module, comprising: a plurality of battery cells; and A composition according to any one of claims 1 to 17 disposed between the battery cells.

20. A battery module, comprising: a plurality of battery cells; and The fire extinguishing assembly according to claim 18 is disposed between the battery cells.

Citation Information

Patent Citations

  • Modified ultrastable Y (USY) zeolite catalyst for improving low-temperature flow characteristics of distillate

    KR1020220125266A

  • Filters for fluid filtration, bypass valve devices for filters and diffuser devices for filters

    KR1020220125271A

  • Ultrasonic scanner for scanning an interior of offshore structures and ships including the same

    KR1020230041417A